2021
DOI: 10.3847/1538-4357/abdd2c
|View full text |Cite
|
Sign up to set email alerts
|

Reflection Modeling of the Black Hole Binary 4U 1630–47: The Disk Density and Returning Radiation

Abstract: We present the analysis of X-ray observations of the black hole binary 4U 1630−47 using relativistic reflection spectroscopy. We use archival data from the Rossi X-ray Timing Explorer, Neil Gehrels Swift Observatory, and Nuclear Spectroscopic Telescope Array observatories, taken during different outbursts of the source between 1998 and 2015. Our modeling includes two relatively new advances in modern reflection codes: high-density disks, and returning thermal disk radiation. Accretion disks around stellar-mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 64 publications
3
38
0
Order By: Relevance
“…The drop in inner disk temperature and increase in R in in the soft-to-hard transition indicate that softer reflected emission due to self-irradiation is associated with a hotter disk with a smaller inner radius. The spectral results for an outburst of the black hole binary (BHB) 4U 1630-47 (Connors et al 2021) also found this association for the soft state.…”
Section: Spectral Results Through State Transitionmentioning
confidence: 69%
See 1 more Smart Citation
“…The drop in inner disk temperature and increase in R in in the soft-to-hard transition indicate that softer reflected emission due to self-irradiation is associated with a hotter disk with a smaller inner radius. The spectral results for an outburst of the black hole binary (BHB) 4U 1630-47 (Connors et al 2021) also found this association for the soft state.…”
Section: Spectral Results Through State Transitionmentioning
confidence: 69%
“…The latter includes the calculation of the relativistic effects that distort the spectrum, such as light-bending effects, Doppler shifts, and gravitational redshifts. However, some previous studies (e.g., the study of BHXRB XTE J1550 −564; Connors et al 2020, BHXRB 4U 1630Connors et al 2021) have found that the coronal inverse-Compton (IC) reflection model does not adequately describe the reflection continuum, and it is necessary to have an alternative model that adopts a softer, thermal continuum as its irradiating spectrum. It was found that the reflection spectrum in the very soft state is best explained by disk self-irradiation, meaning photons from the inner disk are bent by the strong gravity of the black hole and reflected off the disk surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works bySridhar et al (2019Sridhar et al ( , 2020 andConnors et al (2020Connors et al ( , 2021 have tracked the inner accretion flow properties of microquasars across the bright, ballistic jet-emitting states during an X-ray outburst with state-of-the-art X-ray reflection models, and have demonstrated that the inner edge of the accretion disk extends to R in ∼ R isco at these states.19 Classical mechanisms including Newtonian precession were one of the initial interpretations of the observed super-orbital modulation(Katz 1973;Levine & Jernigan 1982;Katz et al 1982). …”
mentioning
confidence: 99%
“…The coronal emission starts to dominate the disk illumination above ∼5 keV. Models of this type may explain the recently reported evidence for returning radiation in spectral fits of the sources 4U 1630−47 (Connors et al 2021) and XTE J1550−564 (Connors et al 2020). Panel (c) presents the photon indices of the emission irradiating the disk.…”
Section: The Best-fit Cone-shaped Corona Modelmentioning
confidence: 74%
“…Furthermore, we plan to use XILLVER tables derived for input energy spectra that resemble the simulated energy spectra more closely. The blackbody energy spectra described by Connors et al (2021) could be a good starting point. The speed of kerrC could be improved by parallelizing the fitting, with the CPUs of a computer cluster accessing the event data in their shared memorie.…”
Section: Discussionmentioning
confidence: 99%